High-yield bioactive triterpenoid production by heterologous expression in Nicotiana benthamiana using the Tsukuba system - Romsuk, Jutapat; Yasumoto, Shuhei; Fukushima, Ery Odette; Miura, Kenji; Muranaka, Toshiya; Seki, Hikaru (Frontiers in Plant Science, 2022)
Oleanolic acid is a pentacyclic triterpenoid found in numerous plant species and is a precursor to several bioactive triterpenoids with commercial potential. However, oleanolic acid accumulates at low levels in plants, and its chemical synthesis is challenging. Here, we established a method for producing oleanolic acid in substantial quantities via heterologous expression of pathway enzymes in Nicotiana benthamiana. The "Tsukuba system" is one of the most efficient agroinfiltration-based transient protein expression systems using the vector pBYR2HS, which contains geminiviral replication machinery and a double terminator for boosting expression. In this study, we evaluated the applicability of this system to heterologous triterpenoid production in N. benthamiana. Medicago truncatula cytochrome P450 monooxygenase (CYP) 716A12 is the first enzyme to be functionally characterized as β-amyrin C-28 oxidase producing oleanolic acid. A mutant CYP716A12 (D122Q) with improved catalytic activity engineered in our previous study was co-expressed with other enzymes in N. benthamiana leaves. Using pBYR2HS, oleanolic acid yield was increased 13.07-fold compared with that using the conventional binary vector, indicating the advantage of the Tsukuba system. We also demonstrated the efficacy of co-expressing a mutant Arabidopsis thaliana HMGR1 catalytic domain, additional NADPH-cytochrome P450 reductase (CPR) transferring electrons to heterologous CYPs, and application of ascorbic acid for preventing leaf necrosis after agroinfiltration, to improve product yield. As a result, the product yields of both simple (β-amyrin) and oxidized (oleanolic acid and maslinic acid) triterpenoids were significantly improved compared with the previously reported yield in heterologous triterpenoid production in N. benthamiana leaves.